2019
DOI: 10.1002/jbt.22374
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effect of Limonin against benzo(a)pyrene‐induced lung carcinogenesis in Swiss albino mice and the inhibition of A549 cell proliferation through apoptotic pathway

Abstract: The main purpose of the current study is to reveal the anticancer action of limonin against benzo(a)pyrene [B(a)P]‐treated lung carcinogenesis in Swiss albino mice and A549 lung cancer cells. B(a)P was orally supplemented (50 mg/kg body weight) twice a week for four weeks induction of lung cancer in mice. The lung weight, body weight, incidence of tumor, lipid peroxidation, carcinoembryonic antigen (CEA), enzymatic and nonenzymatic antioxidants (superoxide dismutase, GPx, glutathione, glutathione reductase, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…It has a variety of biological activities, such as anticancer, antioxidant, anti-inflammatory, neuroprotective, and antibacterial. In recent years, a large number of studies have shown that limonin has great potential in cancer prevention and treatment by scavenging free radicals, stimulating the activity of glutathione transferase, inhibiting the activity of carcinogenic chemicals, and inhibiting the proliferation of tumor cells (Bodduluru et al, 2014;Galal et al, 2015, Gong et al, 2019. These results were similar to the researches of Akihisa et al (2013), Yao et al (2018), andChidambara Murthy et al (2011), which further proved that limonin inhibited the growth of HL-60 cells by inducing apoptosis through mitochondrial-dependent pathway.…”
Section: Discussionssupporting
confidence: 70%
See 2 more Smart Citations
“…It has a variety of biological activities, such as anticancer, antioxidant, anti-inflammatory, neuroprotective, and antibacterial. In recent years, a large number of studies have shown that limonin has great potential in cancer prevention and treatment by scavenging free radicals, stimulating the activity of glutathione transferase, inhibiting the activity of carcinogenic chemicals, and inhibiting the proliferation of tumor cells (Bodduluru et al, 2014;Galal et al, 2015, Gong et al, 2019. These results were similar to the researches of Akihisa et al (2013), Yao et al (2018), andChidambara Murthy et al (2011), which further proved that limonin inhibited the growth of HL-60 cells by inducing apoptosis through mitochondrial-dependent pathway.…”
Section: Discussionssupporting
confidence: 70%
“…It has a variety of biological activities, such as anticancer, antioxidant, anti‐inflammatory, neuroprotective, and antibacterial. In recent years, a large number of studies have shown that limonin has great potential in cancer prevention and treatment by scavenging free radicals, stimulating the activity of glutathione transferase, inhibiting the activity of carcinogenic chemicals, and inhibiting the proliferation of tumor cells (Bodduluru et al., 2014; Galal et al., 2015, Gong et al, 2019). For example, Bae et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The significant drop in the relative lung weight and increased body weight by DAS were consistent with previous chemopreventive studies of various plant extracts and their active components in chemically induced lung cancer. [35][36][37] The histopathological data studies confirmed the tumor growth inhibitory and the protective effect of DAS in the lungs ( Figure 5A). The data also revealed that the pretreatment of DAS controlled the invasion of cancer cells in the liver leading to apoptosis ( Figure 5B).…”
Section: Dovepresssupporting
confidence: 55%
“…In fact, it has been reported that moxa smoke can cause related symptoms, such as eustachian tube and throat itching, eye pain, tonsil enlargement, and other symptoms [ 30 – 33 ]. Tar contains two-tenths of a million of a kind of thick cyclic aromatic hydrocarbon called benzo(a)pyrene, which is a strong carcinogen [ 34 ]. In a few cases, patients undergoing moxibustion treatment or after treatment had erythema, blisters, and other hypersensitive symptoms, and these conditions disappeared after leaving the moxa smoke environment [ 35 – 37 ].…”
Section: Discussionmentioning
confidence: 99%